2022
DOI: 10.18517/ijaseit.12.6.16540
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Security and Perceived Trust on the Use of m-Payment Applications in Saudi Arabia

Abstract: A significant technological revolution is currently occurring, with intense competition between companies to deliver their services via emerging technologies. In Saudi Arabia, mobile payment applications have become more important due to the increasing number of users. By filling in the gaps in the Saudi m-payment setting, this work contributes to the theory. It contributes to practice by giving service providers a clear image of the effects Perceived Security and Perceived Trust have on m-payment apps, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…The study highlights the need of taking cultural variations into account during the technical design stage to make user interfaces more effective. Alotaibi [31] highlighted that in terms of m-commerce consumer loyalty, there were no major variations across gender, age, or experience. Razi et al [32] have found that students are actively engaged in social commerce activities, which impact their purchase intentions and behavior positively.…”
Section: Related Workmentioning
confidence: 99%
“…The study highlights the need of taking cultural variations into account during the technical design stage to make user interfaces more effective. Alotaibi [31] highlighted that in terms of m-commerce consumer loyalty, there were no major variations across gender, age, or experience. Razi et al [32] have found that students are actively engaged in social commerce activities, which impact their purchase intentions and behavior positively.…”
Section: Related Workmentioning
confidence: 99%
“…Random sampling was used to generalize the results ( Alotaibi, 2021 ). Therefore, we used social networks, WhatsApp groups, and Twitter to disseminate 500 questionnaire links to our intended audience.…”
Section: Methodsmentioning
confidence: 99%
“…Technology advances significantly impact societies and businesses ( Alotaibi, 2021 ). For example, in a recent report ( Communications, Space & Technology Commission, 2018 ), 8 million people use sites and applications to buy goods in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Giả thuyết được đề xuất: H6: Sự bồi thường có tác động tích cực đến SHL của KH thế hệ Z Sự liên hệ là khả năng tiếp cận bất kỳ sự hỗ trợ nào từ nhà cung cấp dịch vụ thông qua đại diện trực tuyến hoặc điện thoại21 . Alotaibi tiết lộ rằng khả năng liên lạc có tác động tích cực và đáng kể đến SHL của KH trong mua sắm trực tuyến31 . Tuy nhiên, Çelik đã tìm thấy sự liên hệ không có tác động đáng kể nào đến SHL của KH trong mua sắm trực tuyến tại Thổ Nhĩ Kỳ32 .…”
unclassified
“…Điều đáng ngạc nhiên là bối cảnh tại Việt Nam -một nền kinh tế mới nổi, liên hệ không liên quan đến việc tạo ra SHL của KH trong quá trình mua sắm trực tuyến. Theo Alotaibi, các KH đều cần liên lạc với người bán hàng khi gặp các sự cố ngay lập tức nhằm tạo ra SHL của KH31 , nhưng nó đã không tìm thấy trong nghiên cứu này. Văn hoá của các quốc gia khác nhau có thể dẫn đến các kết quả khác nhau về các thuộc tính và khía cạnh của CLDV điện tử quan trọng để tạo ra SHL của KH.…”
unclassified